The Value of Electrically Evoked Stapedius Reflex in Determining the Maximum Comfort Level of a Cochlear Implant. - Lira de Andrade, Kelly Cristina; Ferreira Muniz, Lilian; de Lemos Menezes, Pedro; Caldas Neto, Silvio da Silva; Lins Carnaúba, Aline Tenório; de Carvalho Leal, Mariana (Journal of the American Academy of Audiology, 2018)
Background: One of the most important steps for good user performance with a cochlear implant (CI) is activation and programming, aimed at determining the dynamic range. In adults, current levels are determined by psychophysical measures. In babies, small children, or individuals with multiple disorders, this procedure requires techniques that may provide inconsistent responses because of auditory inexperience or the age of the child, making it a very difficult process that demands the collaboration of both the patient and the family. Purpose: To study the relationship between the electrically evoked stapedius reflex threshold (ESRT) and maximum comfort level for stimulating electrodes (C-level) in postoperative CI users. Research Design: Cross-sectional analytical observational case series study. Study Sample: We assessed 24 patients of both sexes, aged between 18 and 68 yr, submitted to CI surgery. Intervention: Otoscopy and immittance. Next, an implant speech processor connected to an Itautec® computer containing the manufacturer's software (custom sound Ep 3-2) was used, as well as an AT 235h probe inserted into the ear contralateral to the CI to capture the stapedius reflex, obtaining electrically evoked stapedius reflex thresholds. Data Collection and Analysis: Data from the last programming, defining C-levels for each electrode studied, were extracted from the databank of each patient. The manual decay function of the AT 235h middle ear analyzer was used to observe ESRT response in a same window for a longer response capture time. Electrodes 22, 16, 11, 6, and 1 were tested when active, with the aim of using electrodes over the entire length of the CI, and ESRT was considered present when compliance was ≥0.05 ml. Stimuli, in current units, were always initiated at 20 cu above the C-level. The analysis of variance parametric test, Tukey's honest significant difference test, the t-test, Wilcoxon nonparametric test, and the Kolmogorov-Smirnov test examined whether significant relationships existed between these other factors. Results: The results demonstrate that all the electrodes selected for the study exhibited higher mean reflex threshold values than their mean C-level counterparts. However, there was no significant difference between them, for electrodes 1, 6, 11, and 16. The data provided allow the use of ESRT to define C-level values and make it possible to stipulate a correction factor ranging between 6 and 25.6 electrical units. Conclusion: The use of electrically evoked stapedius reflex thresholds can help the team in charge of programming CIs, making the process faster and safer, mainly for infants, small children, or individuals with multiple disorders.